2016
DOI: 10.1039/c6ra00070c
|View full text |Cite
|
Sign up to set email alerts
|

A waxberry-like SiO2@MnSiO3 core–shell nanocomposite synthesized via a simple solvothermal self-template method and its potential in catalytic degradation and heavy metal ion removal

Abstract: A novel waxberry-like SiO2@MnSiO3 core–shell nanocomposite was facilely fabricated via the simple one-step thermal treatment of SiO2 nanospheres, MnCl2·4H2O, ethylenediamine (EDA), and ethylene glycol (EG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In addition, the b value of IIP‐PEI/CM (0.057) is also higher than that of NIP‐PEI/CM (0.010), which suggests that IIP‐PEI/CM has more affinity towards W(VI) in comparison with NIP‐PEI/CM. These results indicate that the binding process of W(VI) onto IIP‐PEI/CM or NIP‐PEI/CM is restricted to a monolayer adsorption, and the binding sites on the membrane surface are uniform …”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, the b value of IIP‐PEI/CM (0.057) is also higher than that of NIP‐PEI/CM (0.010), which suggests that IIP‐PEI/CM has more affinity towards W(VI) in comparison with NIP‐PEI/CM. These results indicate that the binding process of W(VI) onto IIP‐PEI/CM or NIP‐PEI/CM is restricted to a monolayer adsorption, and the binding sites on the membrane surface are uniform …”
Section: Resultsmentioning
confidence: 85%
“…It can be found that, after three cycles, the rejection ratio of W(VI) declines from 98.1% to 94.3% with only 3.87% loss of initial rejection ratio. Such phenomenon is probably due to the loss of small amounts of binding sites during the operation and cleaning processes . The rejection ratio still keeps at a high value after the cycle tests, disclosing the good surface composition and chemical stability of IIP‐PEI/CM.…”
Section: Resultsmentioning
confidence: 93%
“…To further study the catalytic performance, Table 1 lists the rate constants and the consumption of MB caused by 1 g catalyst and 1 L 30 wt% H 2 O 2 solution. At 60 °C and the dosage of H 2 O 2 of 3 mL, there are an optimal rate constant (≈0.828 min −1 ) and Q value (81.9 g L −1 g −1 ), 530% higher than those of SiO 2 @MnSiO 3 which included adsorption and catalytic processes . Such a superior performance is attributed to the hollow tubular structure with open ends and mesoporous walls.…”
Section: Resultsmentioning
confidence: 97%
“…Where C t and k are the concentrations of MB at the time t and the rate constant, respectively . The catalytic efficiency can also be evaluated by Q Q=(C0C)V0/Vm…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation